SYSTEMATIC LITERATURE NETWORK ANALYSIS OF THE “INNOVATION POLICY MIX” CONCEPT: EXTENDING LEADERS’ VIEWS ON ORGANIZATIONAL ENVIRONMENT - Edwin Rommel; Amin Wibowo; Nurul Indarti; Ely Susanto (Journal of Leadership in Organizations, 2021)
Introduction/Main Objectives: This study aims to depict the scientific landscape for the innovation policy mix (IPM) from 2012 to 2019 since its re-conceptualization by Flanagan, Uyarra, and Laranja (2011).Background Problems: The seminal work has broadened policy mix thinking with social issues impacting innovation. Since every organization is part of the innovation policy system, this study takes the first step to introduce IPM into management fields by identifying and discussing subsequent works in research trajectories.Novelty: This study shows the remarkable progress toward a mature concept through IPM’s definition, characteristics, and boundaries. As a new string of interdisciplinary social science research, some opportunities and challenges are revealed, allowing future studies to be conducted in more theoretically sounding research traditions.Research Methods: This study applies systematic literature network analysis (SLNA) relying on objective measures from keyword co-occurrences and co-citations networks. It includes 60 articles analyzed using open-source software, i.e., Publish or Perish, Google Scholar database, VOSviewer, and the web-based Local Citation Network.Finding/Results: There are three clusters in the main path of research trajectories, i.e., IPM’s conceptualization, its characteristics for evaluation and measurement, and contextualization. Future research directions are proposed to advance our understanding of the organizational environment and its impact on innovation.Conclusion: IPM studies have opened opportunities to test and extend theories in strategic management and organization studies, especially for leaders who make decisions in the face of dynamic and demanding environments. Moreover, contextualization in developing countries would be a worthwhile exercise by considering the institutional and cultural context.